Peningkatan Gaya Hidup Bersih dan Sehat Melalui Bakti Sosial dan Sosialisasi di Panti Asuhan Dharma Jati Klungkung - Yukiandani, Ni Putu Eviana; Laksmi, Putu Cahya Putri Sri; Suasnawa, I Gede; Sutrisnawati, Ni Nyoman Dwi; Suandari, Putu Vierda Lya; Nugraha, I Nyoman Adikarya (STIKES Yayasan RS.Dr.Soetomo, 2025)
Social service and outreach activities carried out by the Hospital Administration Student Association (HIMARS) of Bali International University are one part of the work program. In this activity, HIMARS distributed packages of necessities to children in orphanages as a form of concern for the welfare of others. To ensure continuity, HIMARS has designated this activity as a routine part of the work program carried out every year. Social service and outreach activities at the Dharma Jati Klungkung Orphanage are carried out with the aim of increasing the knowledge and understanding of orphanage children regarding PHBS and increasing caring attitudes towards fellow citizens, as well as a routine program from HIMARS. The social service and outreach method used is by coming directly to the orphanage to hand over packages of needs and providing outreach material about PHBS, hand washing practices and cough and sneeze etiquette. Based on the results of surveys and evaluations using pretest and posttest methods, there was a significant increase in children's knowledge about PHBS, from an average score of 70 in the pretest to 90 in the posttest. This shows that health education programs carried out intensively and participatively can bring positive changes in the healthy living habits of children in orphanages.